The Efficient Storage of Text Documents in Digital Libraries - Skibiński, Przemyslaw; Swacha, Jakub (Information Technology and Libraries, 2009)
In this paper we investigate the possibility of improving the efficiency of data compression, and thus reducing storage requirements, for seven widely used text document formats. We propose an open-source text compression software library, featuring an advanced word-substitution scheme with static and semidynamic word dictionaries. The empirical results show an average storage space reduction as high as 78 percent compared to uncompressed documents, and as high as 30 percent compared to documents compressed with the free compression software gzip.